Growth and characterization of transition metal dichalcogenides: from monolayers to heterostructures - Wang, Xingli (2016)
Semiconducting transition metal dichalcogenide monolayers (molybdenum disulfide (MoS2) and diselenide (MoSe2), and tungsten disulfide (WS2) and diselenide (WSe2) and their heterostructures have shown good performance in field effect transistors, optoelectronics and flexible devices. However, the lack of the preparation of these monolayers and heterostructures with large area and high quality restrict their practical application. Chemical vapor deposition (CVD) has shown strength on the growth of various two dimensional materials, and are suitable to the growth of these transition metal dichalcogenide monolayers and heterostructures with large area and high quality. In this work, the growth of different monolayers (MoS2, MoSe2 and WS2) with CDV method is explored. And both vertical and lateral heterostructures based on MoS2 and WS2 monolayers have also been synthesized with CVD method as well. Raman, photoluminescence, scanning transmission electron microscopy and electrical transport measurement prove high quality of these CVD grown materials.